2010
DOI: 10.3904/kjim.2010.25.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Low Doses of Rosuvastatin and Atorvastatin on Lipid and Glycemic Control in Patients with Metabolic Syndrome and Hypercholesterolemia

Abstract: Background/Aims:This multicenter, open-labeled, randomized trial was performed to compare the effects of rosuvastatin 10 mg and atorvastatin 10 mg on lipid and glycemic control in Korean patients with nondiabetic metabolic syndrome. Methods: In total, 351 patients who met the modified National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria for metabolic syndrome with low-density lipoprotein cholesterol (LDL-C) levels ≥ 130 mg/dL were randomized to receive either rosuvastatin 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
6
28
0
Order By: Relevance
“…21 Park et al, in the study with 351 Korean patients with metabolic syndrome and hypercholesterolemia found greater reduction in TC and LDL-C level by Rosuvastatin treatment as compared to Atorvastatin treatment which is similar with the result of my study. 22 A 48 week randomized, parallel group, open label study done in 106 patients with primary hypercholesterolemia by Mazza et al, showed that Rosuvastatin was associated with significantly greater reduction in LDL-C, TC, and TG compared to Atorvastatin which resembles with the result of my study. 23 A comparative study done by Otokozawa et al, also showed that maximum dose Rosuvastatin 40mg/day was significantly more effective than Atorvastatin 80mg/day in reducing LDL-C, TG and TC which supports the result of my study.…”
Section: Discussionsupporting
confidence: 76%
“…21 Park et al, in the study with 351 Korean patients with metabolic syndrome and hypercholesterolemia found greater reduction in TC and LDL-C level by Rosuvastatin treatment as compared to Atorvastatin treatment which is similar with the result of my study. 22 A 48 week randomized, parallel group, open label study done in 106 patients with primary hypercholesterolemia by Mazza et al, showed that Rosuvastatin was associated with significantly greater reduction in LDL-C, TC, and TG compared to Atorvastatin which resembles with the result of my study. 23 A comparative study done by Otokozawa et al, also showed that maximum dose Rosuvastatin 40mg/day was significantly more effective than Atorvastatin 80mg/day in reducing LDL-C, TG and TC which supports the result of my study.…”
Section: Discussionsupporting
confidence: 76%
“…Similar findings were shown for pravastatin, which is nonlipophilic 22,23. Another study compared the effects of atorvastatin (10 mg) and rosuvastatin (10 mg) on changes in glucose and insulin levels, and the HOMA of the insulin resistance index, which were not significantly different between the two groups 24. Also, the result of a meta-analysis of randomized controlled trials may suggest that potential differences exist between statins 25.…”
Section: Discussionsupporting
confidence: 54%
“…Our study demonstrates for the first time that rosuvastatin may improve IS in non‐diabetic patients compared with atorvastatin. Other comparative studies did not show changes in IR (5,6). The two statins had neutral impact on HbA 1c in our study with a trend towards reducing fasting plasma glucose levels (mainly with rosuvastatin).…”
Section: Discussionmentioning
confidence: 78%